Economic Potential of Cultural Tourism In Terms of Tourism Marketing (International Journal of Engineering and Computer Science, 2018)
The concept of tourism marketing includes all activities related to marketing of the tourism sector. In tourism marketing, all activities which are applied to ensure participation of the customer who is referred as “tourist” in the tourism movements and satisfaction of this customer constitute the basic element of the mentioned concept.